Die Entwicklung der östlichen Po-Ebene seit frühgeschichtlicher Zeit - Dongus, Hansjörg (ERDKUNDE, 1963)
The eastern lowland of the Po river consists of relatively dry marginal plateaux and an also dry central part, the so-called Terre vecchie which, owing to its height is drained naturally. Between the Terre vecchie and the dry piedmont gravel plains of the Alps and Apennines broad basins at altitudes above sea level are interposed, enclosed by the high river levees, and these require artificial drainage. Up to 60 years ago they were covered by freshwater marshes (Valli dolci, inner Valli). Eastwards of the Terre vecchie follows a zone of marsh, haffs or lagoons, lying below sea level, now also improved but prior to drainage brackish-saline water predominated (Valli salse, coastal marshes). The coastal swamps terminate in the east in a storm beach consisting of a number of consecutive ridges. Beyond stretches the recent delta formed in a number of stages since the height of the Middle Ages. The humid reaches of the eastern Po plain, at least the zone of lagoons and coastal swamps, have since Lombardini (1869) so far mostly been explained as a gradually filled-in remnant of a former Sinus Padanus which, in early historical times was separated from the Adriatic Sea by the formation of a sand spit (nehrung, Cordone literale) and was gradually filled by the load of rivers discharging into it. This assumption, however, cannot be reconciled with the fact that along the entire marsh zone traces of settlements, remains from Etruscan and Roman times, have been found below the clays, sands and peat layers of the former coastal swamps at heights which today are generally some metres below sea level. These finds indicate rather an increase in area of the saline Valli since the early Middle Ages. In some cases it must be assumed that they were only formed during the Christian era. The low position of the remains points towards a post-Roman relative rise of the sea level of the order of 4-5 metres. This rise was probably largely of a eustatic nature but it was very likely accompanied and enforced by a subsidence of the land. Because of this rise of the sea level extensive parts of the eastern plain of the Po came in historical times to lie below mean water and thus became marshy. Owing to the simultaneous rise in height of the river levees, the basins of the inner valli, situated above sea level, also became swampy since their drainage had become retarded because of the rise of the base level. The coastal swamps and lagoons of the north-western Adriatic Sea must therefore be taken as formations of transgression not of regression of the sea. A confirmation of this working hypothesis will, however, only be possible by sediment-petrographical analyses.